2013
DOI: 10.1073/pnas.1311217110
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide fitness profiling reveals adaptations required by Haemophilus in coinfection with influenza A virus in the murine lung

Abstract: Bacterial coinfection represents a major cause of morbidity and mortality in epidemics of influenza A virus (IAV). The bacterium Haemophilus influenzae typically colonizes the human upper respiratory tract without causing disease, and yet in individuals infected with IAV, it can cause debilitating or lethal secondary pneumonia. Studies in murine models have detected immune components involved in susceptibility and pathology, and yet few studies have examined bacterial factors contributing to coinfection. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 54 publications
3
56
0
Order By: Relevance
“…41,42 This has also been confirmed in numerous preclinical studies. 43,44 Previous reports have shown that radiologically confirmed pneumonia is associated with severe outcomes. 3,4,8,20,32 Although multivariate analysis did not reveal that pneumonia on admission was a significant clinical risk factor for a severe outcome in our study, it is noteworthy that 64% of subjects with 2009 H1N1 had infiltrates on x-rays at admission (92% for ICU subjects) compared with 17% of subjects presenting with an influenzalike illness, underlining its significance in complicating the confirmed cases requiring hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 This has also been confirmed in numerous preclinical studies. 43,44 Previous reports have shown that radiologically confirmed pneumonia is associated with severe outcomes. 3,4,8,20,32 Although multivariate analysis did not reveal that pneumonia on admission was a significant clinical risk factor for a severe outcome in our study, it is noteworthy that 64% of subjects with 2009 H1N1 had infiltrates on x-rays at admission (92% for ICU subjects) compared with 17% of subjects presenting with an influenzalike illness, underlining its significance in complicating the confirmed cases requiring hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The recent application of “deep sequencing” to the challenge of tracking the relative abundance of various transposon insertion mutants in multiplex analyses has provided an exciting high-throughput negative selection approach to comprehensively identify genes required for selectable phenotypes (Chao et al, 2013; Dong et al, 2013; Gallagher et al, 2011; van Opijnen and Camilli, 2013; Wong et al, 2013; Zhang et al, 2012). Ordered transposon insertion libraries also can facilitate comprehensive analysis of pathogen-host interactions as well as provide investigators with an opportunity to “cherry pick” mutants for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Figure prepared with PyMOL (http://www.pymol.org/). influenza A virus [77]. Furthermore, IscR function on Vibrio vulnificus highly impacted its motility and adhesion to host cells, hemolytic activity, and survival under oxidative stress during infection [10].…”
Section: Implications Of Iscr In Host-pathogen Interactionsmentioning
confidence: 99%